2009 4th International IEEE/EMBS Conference on Neural Engineering 2009
DOI: 10.1109/ner.2009.5109238
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of blink in facial paralysis patients using FES

Abstract: Six subjects with profound facial paralysis were tested to determine the feasibility of restoring functional blink via electrical stimulation of the orbicularis oculi muscle (OOM) without also evoking painful sensations.Stimulation of the paretic eyelid was triggered by EMG detection of blink in contralateral healthy OOM to deliver charge during inhibition of the levator palpebrae antagonist. Transcutaneous and percutaneous stimulation electrode placements were tested during multiple stimulation trials in subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…A prior study observed that rabbits initially flinched in response to orbicularis oculi stimulation, but signs of pain diminished over time (Otto, 1997). There is evidence that FES paradigms including interferential stimulation (McDonnall et al, 2009) and low-intensity multichannel stimulation (Somia et al, 2001) render facial muscle stimulation functional but not painful. Finally, facial FES has been achieved in humans reporting only mild pain (McDonnall et al, 2009; Frigerio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prior study observed that rabbits initially flinched in response to orbicularis oculi stimulation, but signs of pain diminished over time (Otto, 1997). There is evidence that FES paradigms including interferential stimulation (McDonnall et al, 2009) and low-intensity multichannel stimulation (Somia et al, 2001) render facial muscle stimulation functional but not painful. Finally, facial FES has been achieved in humans reporting only mild pain (McDonnall et al, 2009; Frigerio et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on contralaterally-triggered facial FES has been done in larger animal models and humans over the course of several decades (Zealear and Dedo, 1977; Tobey and Sutton, 1978; Broniatowski et al, 1987, 1989, 1991; Cao et al, 2009; McDonnall et al, 2009; Kurita et al, 2010; Frigerio and Cavallari, 2012). However, the therapy has not advanced beyond proof of concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A team based at Ripple, llc (Salt Lake City, UT) is developing a fully implantable system for restoration of eye-blink in hemiparalysis patients [52]. The overall concept of the device is to record electromyographic (EMG) signals from a small electrode implanted in the orbicularis oculi muscle on the healthy side of the face [53].…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…Previous studies have shown the feasibility of facial pacing in animal models 1,[4][5][6][7][8][9][10] and in humans. 2,3,11 This work focuses on the recording arm of the loop (ie, detecting blinks). Tracking an infrared light beam passing across the eye surface has been shown to provide a simple, noninvasive indication of eyelid closure in humans.…”
mentioning
confidence: 99%